Advances and controversies in pleural diseases - Porcel, José M.; Statophoulos, Georgios; Lee, Yun Chor Gary (Journal of Thoracic Disease, 2015)
Pleural effusion is a common presentation for many pulmonary and systemic diseases, particularly heart failure, pneumonia, cancer and tuberculosis (TB). An estimated 1.5 million people develop a pleural effusion each year in the United States alone (1). Despite the prevalence of the disease, research in pleural medicine has attracted far less attention than that of much rarer respiratory conditions. Advances in pleural diseases are desperately lacking and far fewer than in other common pulmonary diseases. One paradigmatic example is the use of talc pleurodesis which was first reported in 1935 (2), but remains the standard therapy for symptomatic malignant pleural effusion in most centers. Few, if any, diseases in medicine are now managed in the same way as they were in the 1930’s.